2015
DOI: 10.1021/acs.bioconjchem.5b00041
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of the PEG Corona of Nanoparticles by Clip Photochemistry in Water: Application to the Grafting of RGD Ligands on PEGylated USPIO Imaging Agent

Abstract: The fast development of nanomedicines requires more and more reliable chemical tools in order to accurately design materials and control the surface properties of the nano-objects used in biomedical applications. In this study we describe a smooth and simple photografting technique, i.e., the clip photochemistry, that allows the introduction of molecules of interest in inert polymers or on stealth nanoparticles directly in aqueous solution. First we developed the methodology on polyethylene glycol (PEG) and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The restrained diffusion of water molecules across the phospholipid barrier is moreover responsible for r 1 drop due to the absence of direct contact with the magnetic core [68]. Similar decreases of r 1 at higher magnetic fields for SPIONs were noticed previously [69,70]. The obtained relaxivity values indicated that these MNP have a much larger r 2 compared to r 1 and, therefore, they could be used as negative contrast agents in MRI studies, according to our findings.…”
Section: Discussionsupporting
confidence: 85%
“…The restrained diffusion of water molecules across the phospholipid barrier is moreover responsible for r 1 drop due to the absence of direct contact with the magnetic core [68]. Similar decreases of r 1 at higher magnetic fields for SPIONs were noticed previously [69,70]. The obtained relaxivity values indicated that these MNP have a much larger r 2 compared to r 1 and, therefore, they could be used as negative contrast agents in MRI studies, according to our findings.…”
Section: Discussionsupporting
confidence: 85%
“…The absolute sensitivity of 19 F is ~4700 times higher than 13 C, and only ~12% lower than 1 H. Furthermore, 19 F has negligible background interference, and the spectra are relatively simple. Quantitative 19 F NMR ( 19 F qNMR) has found important uses in quantification of fluorinated compounds in complex matrices, [36][37][38] , polymers grafted on nanoparticles, 39 and for the quan-2 titative measurement of enzymatic activity by determining released fluorinated groups from nanomaterials. [40][41][42][43][44] There has been no report on applying 19 F qNMR for the analysis of carbohydrate density on glyconanomaterials.…”
mentioning
confidence: 99%
“…Efficient drug and DNA delivery carriers are highly needed in pharmacology, medicine, and biotechnology. In recent years, different systems have been developed for this purpose, e.g., lipid based nanocapsules , polymersomes , or surface‐conjugated nanoparticles . In all cases, the delivery of the cargo is a complex, multistep process: particles have to reach their targets, enter into the cells, in most cases by endocytosis, escape the endosomal membrane, and release the cargo which has to bind on the correct site .…”
mentioning
confidence: 99%